Gaint Haematoma After Pilonidal Sinus Operation Due To Factor VII Deficiency: A Case Report - Menteş, Öner; Nevruz, Oral; Bozoğlu, Ergun; Çankır, Zeki; Özgül, Ömer; Özdemir, Mustafa (Fırat University, 2007)
Pilonidal sinus disease is usually occurs in the intergluteal region. Many surgical techniques have been described for treatment of this disease. A main surgical complication after operation is infection, while haematoma, on the other hand, is a rare complication. Factor VII deficiency is an uncommon bleeding disorder with an estimated incidence of 1/500.000. We report a case with giant haematoma 2 years after pilonidal sinus operation with out any trauma. Heterozigot Factor VII deficiency is diagnosed with laboratory tests. The patient was discussed in the view of the literature knowledge. ©2007, Firat University, Medical Faculty

Pilonidal sinüs hastalığı intergluteal bölgede oluşan hastalıktır. Tedavisi için pek çok cerrahi yöntem tanımlanmıştır. Cerrahi sonrası en çok karşılaşılan komplikasyon enfeksiyondur. Geç dönemde hematom oluşumu çok ender rastlanan komplikasyondur. Faktör VII eksikliği, 1/500.000 gibi oldukça ender görülen doğumsal kanama diatezi nedenlerinden birisidir. Bu yazıda pilonidal sinüs hastalığı nedeniyle primer eksizyon ve kapama operasyonu olan hastada travma olmaksızın iki yıl sonra gelişen dev hematom saptanması ve yapılan tetkiklerinde heterozigot Faktör VII eksikliği tanısı konulan olgu literatür eşliğinde tartışılarak sunuldu. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Pilonidal Sinus Cerrahisi Sonrası Faktör VII Eksikliği Nedeniyle Geç Dönemde Ortaya Çıkan Dev Hematom: Olgu Sunumu